HUBUNGAN MINAT MEMBACA BUKU ILMU UKUR TANAH DENGAN PRESTASI BELAJAR ILMU UKUR TANAH SISWA SMK NEGERI 1 PADANG - 8-16 . Alvina (Universitas Negeri Padang, 2013)
The background of this research is the lack of interest in reading books Science of Geometery Land Competency Skills class X Architecture at SMK Negeri 1 Padang. The study aims to determine the relationship between interest in reading books Science of Geometery Land learning achievement Science of Geometery Land Competency Skills class X Architecture SMK Negeri 1 Padang. This research is a descriptive study is correlational. The research hypothesis is,